P009: Quality improvement and implementation of urine culture follow up process. (May 2020) - Walji, N.; Greer, A.; Hewitt, M.; BinKharfi, M.
Abstract : Background: The diagnosis of urinary tract infection (UTI) is made based on symptoms, urinalysis and urine culture. While simple urinary tract infections do not require routine culture, the Infectious Disease Society of America (IDSA) Guidelines state that complicated urinary tract infections should have urine cultures performed to determine which antibiotics are effective, as there is a higher risk of infection with resistant organisms. We hypothesized that the rate of urine cultures sent for complicated UTI is less than is recommended by the literature. Aim Statement: We aimed to implement a follow-up reporting system for Urinary Culture in patients diagnosed with complicated UTIs and raise our Urinary Culture rates in this population to 80% by June 2019. Measures & Design: We performed a single-center chart review using Emergency Department (ED) charts of non-admitted patients. They were audited daily for two weeks to obtain a sample of patients who had a discharge diagnosis of urinary tract infection, pyelonephritis or cystitis. Charts capturing these diagnoses were assessed to see if a culture was clinically indicated and if it was ordered. Charts were screened for the presence of any of the following criteria indicating complicated UTI: known structural or functional abnormality of the urinary tract, genitourinary obstruction, pregnancy, immunosuppression, diabetes, indwelling or intermittent catheter use, fever, male patient, clinical pyelonephritis, antimicrobial failure, or transfer from a nursing home. Data was then compiled to determine culture rates in complicated and uncomplicated UTIs. This prevalence rate established the baseline performance in the ED which was used to inform the quality improvement project. Evaluation/Results: Over a two week period, 26 patients were discharged from the ED with a diagnosis of UTI, with 17 of these patients meeting criteria for complicated UTI. Only 6 of 17 complicated UTIs were sent for urine culture, therefore our pre-implementation culture rate was 35%. After initial data collection, a follow-up system was designed ensuring that urine culture and sensitivities results would be compiled and reviewed daily at Hamilton Health Sciences. This system was created with input from key stakeholders including department chiefs, core lab services, ED physicians and business clerks. A discrepancy form was created for documentation of culture result recognition and any required patient follow up ie. antibiotic change. In October 2019, the system had been implemented for a month, after which another chart review was completed. 27 cases were captured, 18 of which were complicated. The complicated culture rate had increased significantly from 35% to 72%. Discussion/Impact: In the ED, ordering of cultures for patients being discharged, regardless of type, is commonly associated with concern of result follow up, which may take up to 72 hours. This discrepancy system was implemented to ensure that all urine cultures ordered had appropriate follow up, thus supporting physicians in ordering cultures when indicated. The significant improvement in culture rate from 35% to 72% is balanced by one single culture of all 9 simple UTIs (11%). In PDSA cycle 2, we hope to increase rates to 90% by improving current challenges with the system.